Improving implementation of occupational health and safety of construction company by Job Safety Analysis (JSA) method (study case at PT Arto Moro Sentosa) - Sulistyo, Arif Budi; Putra, Nugroho Pratama; Wijaya, Hartadi; Hidayanti, Nur (OPSI, 2024)
The construction sector is a sector that employs many people who have high risk of work accidents, because a lot of work in this sector is possibility carried out by unsafe actions or unsafe conditions. PT. Arto Moro Sentosa is company which operates in general trading, general construction, suppliers, outsourcing, etc., is aware that the business has a high risk of work accidents. The lack of employee awareness will have an impact on the magnitude of the risks that must be borne by the worker and the company. The purpose of this research is determining work accident records for the Occupational Health and Safety (OHS) system, employee risks, and existing improvements at company. By knowing the classification of hazards based on the type of accident, this research uses the Job Safety Analysis (JSA) method, histograms, Pareto diagrams, and cause-and-effect (fish bone) diagrams. Based on the author's observations, company data related to OHS (Occupational Health and Safety) and interviews with the directors, could be obtained a history of work accidents based on the type of accident. Here are ergonomic work accidents (57.89%), physical factor accidents ( 31.58%), chemical factor accidents (5.26%), biological factor accidents (5.26%), and psychological factor accidents (0%). Several recommendation is performed to avoid repeated accident by providing training programs on OHS to workers, paying more attention to OHS supervision, giving sanctions to workers who violate OHS.